Bonaparte falls apart - Cuyler, Margery; Terry, Will, 1966- (New York : Crown Books for Young Readers, 2017)
Bonaparte the skeleton is literally falling to pieces and needs help from his friends to pull himself together before the first day of school.
Keywords: Skeleton -- Fiction; Monsters -- Fiction; Self-confidence -- Fiction; Friendship -- Fiction; First day of school -- Fiction; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Social Issues / Friendship; JUVENILE FICTION / Monsters